Frank Lloyd Wright, architect an illustrated biography - Boulton, Alexander O. (New York Rizzoli International Publictions, Inc., 1993)
Traces the life and work of the twentieth-century American architect who called his innovative ideas "organic architecture."
Co-published with the Frank Lloyd Wright Foundation
Keywords: Wright, Frank Lloyd -- 1867-1959 -- Juvenile literature; Architects -- United States -- Biography -- Juvenile literature